PENGARUH AGRESIVITAS PAJAK TERHADAP REAKSI PASAR DENGAN DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Anthony Holly (Universitas Katolik Indonesia Atma Jaya, 2021)
The purpose of this study was to investigate the effect of Tax Aggressiveness on Market Reactions with the Independent Board of Commissioners as Moderating Variables. High and Low Market Reactions can be influenced by Tax Aggressiveness. This study aims to determine the effect of Tax Aggressiveness on Market Reactions and to find out whether Independent Board of Commissioners are able to weaken or strengthen the relation of Tax Aggressiveness to Market Reactions. This study uses observation methods in non-financial companies listed on the Indonesia Stock Exchange for the period 2015-2017. The population in this study amounted to 559 companies. The sample selection uses a purposive sampling technique, so that a total sample of 125 companies was obtained. The Moderated Regression Analysis (MRA) test is used in this research. The results of this study indicate that tax aggressiveness has a negative and significant effect on market reaction. The Independent Board of Commissioners strenghten the relation of Tax Aggressiveness to Market Reactions.